iPhone & iPad web design for dummies - Warner, Janine , 1967-; Andron, Lee; LaFontaine, David (--For dummies, 2011)
Overview: A full-color guide to designing cutting-edge web sites for the iPhone, iPad, and iPod touch! Apple's touchscreen devices have created worldwide techno-lust, conjuring a record-breaking market out of thin air. iPads, iPhones, and iPods are so in demand that they outsell every other device in their categories. If your website is not designed to take advantage of the extraordinary new capabilities of these popular devices, then you will miss out on an increasingly important part of your audience. With all the focus on the App Store (thanks to the ubiquitous "There's an App for that-" ad campaign), you could be forgiven for overlooking the fact that the single most popular app on the iPhone and iPad is Safari. That's right. The humble web browser that comes installed on every iOS device, ready to surf at the flick of a finger. This is where iPhone & iPad Web Design For Dummies comes in. Based on real-world experience, this guide (written in a language that real human beings can read) shows you how to use HTML5, CSS3, and jQuery to produce interactive websites that will delight your users and keep them coming back for more. You'll discover how to plan the perfect mobile web experience, create interactivity and multimedia, test and optimize your creations, and publish and market your final design with iPhone & iPad Web Design For Dummies!